2019
DOI: 10.7717/peerj.6492
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical content and antioxidant activity in aqueous extracts of Cyclocarya paliurus leaves collected from different populations

Abstract: Cyclocarya paliurus (Batal) Iljinskaja is a multiple function tree species, but its main utilization is for the harvesting of its leaves as materials for tea production and recently as ingredients for the food industry. In this study aqueous extracts of C. paliurus leaves collected from 21 natural populations were evaluated for their phytochemical content and antioxidant activity. The content of water-soluble polysaccharide, total flavonoid and total polyphenol varied from 66.05 to 153.32 mg/g, 9.01 to 19.65 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 37 publications
3
19
2
Order By: Relevance
“…Our results corresponded with previous reports of Liu et al [20] and Zhou et al [17] who indicated that the antioxidant activity of C. paliurus varied with the geographical locations. The ethanol extracts of C. paliurus leaves showed stronger antioxidant capacity than the water extracts, which were in line with the extracts of F. beecheyana and S. chinensis [23,24].…”
Section: Effects Of Solvent and Geographical Origin On Antioxidant Acsupporting
confidence: 93%
See 4 more Smart Citations
“…Our results corresponded with previous reports of Liu et al [20] and Zhou et al [17] who indicated that the antioxidant activity of C. paliurus varied with the geographical locations. The ethanol extracts of C. paliurus leaves showed stronger antioxidant capacity than the water extracts, which were in line with the extracts of F. beecheyana and S. chinensis [23,24].…”
Section: Effects Of Solvent and Geographical Origin On Antioxidant Acsupporting
confidence: 93%
“…Sample solvent (70% ethanol or distilled water) was used as the control. The scavenging capacity of DPPH and 2,2-azino-bis (3-ethylbenzothiazoline-6-sulfonic acid) (ABTS )radicals, and the reducing power were determined and analyzed by the methods described by Zhou et al [17]. The percent inhibition of radical was calculated as ((A control − A sample )/A control ) × 100%, where A control and A sample are the absorbances of the control and sample, respectively.…”
Section: Antioxidant Assaymentioning
confidence: 99%
See 3 more Smart Citations